Radioanatomic Characteristics of the Posteromedial Intraconal Space: Implications for Endoscopic Resection of Orbital Lesions - Jafari, A.; Lehmann, A.E.; Wolkow, N.; Juliano, A.F.; Bleier, B.S.; Reinshagen, K.L. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Imaging is essential in the diagnostic work-up of patients with orbital lesions. The position of an orbital lesion relative to the inferomedial muscular trunk of the ophthalmic artery determines endoscopic resectability, anticipated technical difficulty, and patient morbidity. Although the inferomedial muscular trunk is not readily identifiable on preoperative imaging, we hypothesize that it is spatially approximate to the location where the ophthalmic artery crosses the optic nerve. Our aim was to determine whether the ophthalmic artery–optic nerve crosspoint anatomically approximates the inferomedial muscular trunk in a cadaver study and can be appreciated on imaging of known posteromedial orbital lesions.MATERIALS AND METHODS: Dissection was performed on 17 fresh-frozen cadaver orbits to assess the relationship between the inferomedial muscular trunk and ophthalmic artery–optic nerve crosspoint. Retrospective review of imaging in 9 patients with posteromedial orbital lesions assessed posteromedial orbital compartment characteristics and the ability to locate the ophthalmic artery–optic nerve crosspoint.RESULTS: In our cadaver study, the mean distance between the ophthalmic artery–optic nerve crosspoint and the inferomedial muscular trunk was 1.21 ± 0.64 mm. Retrospectively, the ophthalmic artery–optic nerve crosspoint was identifiable in 9/9 patients, whereas the inferomedial muscular trunk was not identifiable in any patient. Total or partial effacement of the posteromedial intraconal fat triangle was observed in 9/9 patients.CONCLUSIONS: This study of neurovascular relationships within the posteromedial orbit demonstrates that the ophthalmic artery–optic nerve crosspoint closely approximates the inferomedial muscular trunk and can be seen in patients with posteromedial orbital lesions. Posteromedial intraconal fat effacement may help to localize these lesions. These findings may facilitate multidisciplinary communication and help predict lesion resectability and patient outcomes.CECTcontrast-enhanced CTIMTinferomedial muscular trunk of the ophthalmic arteryNECTnon-contrast-enhanced CTOAophthalmic arteryONoptic nerve